2005
DOI: 10.1161/circulationaha.105.533778
|View full text |Cite
|
Sign up to set email alerts
|

Temporally Controlled Onset of Dilated Cardiomyopathy Through Disruption of the SRF Gene in Adult Heart

Abstract: Background-Serum response factor (SRF) is a cardiac transcription factor involved in cell growth and differentiation. We have shown, using the Cre/loxP system, that cardiac-specific disruption of SRF gene in the embryonic heart results in lethal cardiac defects. The role of SRF in adult heart is unknown. Methods and Results-We disrupted SRF in the adult heart using a heart-specific tamoxifen-inducible Cre recombinase.This disruption led to impaired left ventricular function with reduced contractility, subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
157
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(171 citation statements)
references
References 41 publications
(47 reference statements)
13
157
0
1
Order By: Relevance
“…Moreover, deletion of SRF in the adult heart using tamoxifen-induced, Cre-mediated excision results in cardiac failure and death resulting from dilated cardiomyopathy. Consistent with the embryonic phenotypes, adult hearts absent SRF show highly disorganized sarcomeres (81). Finally, a skeletal muscle cKO of SRF (using a myogenin Cre driver) results in perinatal lethality because of dysmyofibrillogenesis in skeletal muscle (61).…”
Section: Genetic Evidence Supporting Srf As a Master Regulator Of Thementioning
confidence: 54%
See 1 more Smart Citation
“…Moreover, deletion of SRF in the adult heart using tamoxifen-induced, Cre-mediated excision results in cardiac failure and death resulting from dilated cardiomyopathy. Consistent with the embryonic phenotypes, adult hearts absent SRF show highly disorganized sarcomeres (81). Finally, a skeletal muscle cKO of SRF (using a myogenin Cre driver) results in perinatal lethality because of dysmyofibrillogenesis in skeletal muscle (61).…”
Section: Genetic Evidence Supporting Srf As a Master Regulator Of Thementioning
confidence: 54%
“…For example, cardiac-restricted overexpression of either wild-type or dominant-negative SRF results in various forms of heart failure because of severe alterations in contractile gene expression (125,126). Moreover, SRF inactivation or knockdown in D. discoideum (26), Drosophila melanogaster (91), Caenorhabditis elegans (30), and Mus musculus (1,28,55,61,70,78,81,82) does not result in impaired cell proliferation. Instead, these SRF null models reveal an essential and ancient role for SRF in the organization of normal cytoskeleton and contractile systems (see below).…”
Section: Serum Response Factor: Toggle Switch For Disparate Programs mentioning
confidence: 99%
“…32,37 A similar ultrastructure phenotype is manifest in adult mouse hearts where SRF is inducibly inactivated using a tamoxifen-responsive Cre recombinase. 38 A mosaic knockout of SRF using the Desmin promoter driving Cre resulted in mutant cardiomyocytes in close apposition to wild-type cardiomyocytes. Despite the presence of some 50% SRF-positive myocytes, mosaic SRF-knockout mice showed increases in both interstitial fibrosis and heart weight to body weight, and eventually succumbed to heart failure by 11 months of age.…”
Section: Srf and Cardiovascular System Disease Heartmentioning
confidence: 99%
“…It is not surprising that SRF activity, must also be tightly regulated through a miR-133 dependent negative feedback loop, because enhanced levels of SRF have led to dilated cardiomyopathy, while too little SRF showed that SRF activity was required for the maintenance of normal sarcomeric organization and contractility (32). Possibly, the delicate balance of miR-133 directed silencing of SRF activity in cardiac hypertrophy may be more profound in human heart disease.…”
Section: Mirna-208 Knockout Revealed a Critical Role In Stress-dependmentioning
confidence: 99%